2004
DOI: 10.1007/bf03033297
|View full text |Cite
|
Sign up to set email alerts
|

Calcium binding protein markers of GABA deficits in schizophrenia — post mortem studies and animal models

Abstract: As quantitative neuroimaging continues to elucidate the gross neuropathology of schizophrenia, neurochemical and histological studies have contributed to defining this pathology in terms of neurotransmitter dysfunction. Increasingly, there is evidence implicating neurons containing the major inhibitory neurotransmitter of the brain--gamma-aminobutyric acid (GABA). Benes was the first to demonstrate deficits in some morphological subtypes of interneurons in the frontal cortex in schizophrenia. We identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 20 publications
12
87
1
Order By: Relevance
“…Moreover, reduced immunoreactivity for PV and/or CB was reported in surviving cerebellar Purkinje cells [21] of patients with spinocerebellar ataxia-1 (SCA-1) and in an animal model using SCA-1 transgenic mice [22]. Decreases in PV expression were one of the most consistent findings in postmortem brains of patients with schizophrenia, bipolar disorder and major depression [23] and also downregulation of CB expression was reported before [24]. The results obtained in human patients and genetically modified mice clearly indicate that the presence or absence of PV or CB has significant effects on synaptic transmission and are likely to have profound effects at the systemic level including behavior, learning or memory.…”
Section: Introductionsupporting
confidence: 61%
“…Moreover, reduced immunoreactivity for PV and/or CB was reported in surviving cerebellar Purkinje cells [21] of patients with spinocerebellar ataxia-1 (SCA-1) and in an animal model using SCA-1 transgenic mice [22]. Decreases in PV expression were one of the most consistent findings in postmortem brains of patients with schizophrenia, bipolar disorder and major depression [23] and also downregulation of CB expression was reported before [24]. The results obtained in human patients and genetically modified mice clearly indicate that the presence or absence of PV or CB has significant effects on synaptic transmission and are likely to have profound effects at the systemic level including behavior, learning or memory.…”
Section: Introductionsupporting
confidence: 61%
“…21). Interestingly, postmortem studies of bipolar disease patients revealed a loss of CB immunoreactivity in the CNS (39). Furthermore, a form of inherited bipolar disease is associated with ataxia (40), and cerebellar ataxia is a common sign of Li ϩ overdosing in the treatment of bipolar disease (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, rodents and nonhuman primates treated with non-competitive NMDAR antagonists display behavioral features consistent with many symptoms of schizophrenia . Repeated dosing with these drugs may provide greater validity than acute administration, as such regimens induce neurochemical changes similar to those seen in schizophrenic patients (Cochran et al, 2003;Enomoto et al, 2005;Reynolds et al, 2004), as well as lasting cognitive deficits that can be observed when animals are tested in a drug-free state (Jentsch and Roth, 1999).…”
Section: Introductionmentioning
confidence: 99%